The Effect of Temperature and Pressure on Filling Time in the Injection Process of Shop Hanger Products - Thedy Kristanto; Paryanto; Heri Wibowo (Journal of Applied Mechanical Engineering Innovation, 2025)
This study investigated the effect of melt temperature and injection pressure on filling time in the injection molding process for shop hanger products. The research used an experimental simulation method with Autodesk Moldflow Adviser 2023. The melt temperature was varied at 180, 190, 200, 210, and 220 °C, while injection pressure was varied at 20, 30, 40, and 50 MPa. Runner diameters of 2, 4, and 6 mm were also evaluated to determine the most suitable flow channel for the mold design. The results show that a 4 mm runner produced the shortest filling time among the runner variations. Increasing temperature and pressure tended to reduce filling time within the tested parameter range. The shortest filling time was obtained at a melt temperature of 220 °C and an injection pressure of 40 MPa with a 4 mm runner. Several defects, including short shot, warpage, weld lines, sink marks, and air traps, were detected during the simulation, but the defects were not significant under the optimal parameters. The mold was designed with a 330 × 350 mm mold base and a required clamping force of 470 kN. The selected injection machine available at CV. Mulus Teknik, a 90-ton UN90SKII machine with a clamping force of 900 kN, was suitable for production.